FRI0073 Diagnostic performance of the 2010 ACR/EULAR classification criteria for rheumatoid arthritis in a cohort of early arthritis. (23rd January 2014) - Sakellariou, G.; Scirè, C.A.; Montecucco, C.; Caporali, R.
Abstract : Background: Early diagnosis is a central issue in the management of rheumatoid arthritis (RA), and the insufficient sensitivity of the 1987 American College of Rheumatology (ACR) classification criteria in this setting led ACR and the European League Against Rheumatism (EULAR) to develop in 2010 a new set of classification criteria, based and validated on data from early arthritis (EA) patients. These criteria need further validation in external cohorts. Objectives: To evaluate the diagnostic performance of The ACR/EULAR 2010 classification criteria for RA in EA patients, with the use of methotrexate (MTX) or disease modifying antirheumatic drugs (DMARDs) 12 months after diagnosis as reference standard. Methods: Patients with RA, according to the 1987 ACR criteria, or undifferentiated polyarthritis (UPA), attending for the first time an Early Arthritis Clinic, were enrolled. Patients with RA were given methotrexate (MTX), while patients with UPA received hydroxichloroquine (HCQ). Other synthetic DMARDs (sulphasalzine, leflunomide, cyclosporine) were given in case of contraindications or intolerance to MTX. Patients were seen every two months in the first semester and every three afterwards. Patients on HCQ were switched to MTX and MTX escalated up to 20 mg/week if Disease Activity Score was ≥2.4 at subsequent visits. If disease activity was not sufficiently controlled by conventional DMARDs, biologic DMARDs were added. ACR/EULAR 2010 classification criteria were applied at baseline and the use of MTX or synthetic or biologic DMARDs was evaluated after 12 months of treatment. Only patients with complete data were included. Results: 266 patients were included, 74% female, mean age (sd) was 57.2 (±14.3), median (IQR) disease duration was 3.07 (1.2, 7.1) months, 33% of patients were rheumatoid factor positive, 66.9% patients fulfilled the 1987 RA classification criteria. ACR/EULAR 2010 classification criteria were fulfilled by 76.69% of patients at baseline, 1987 and 2010 criteria showed a moderate agreement (78.2%). After 12 months 211/266 (73.68%) patients were taking DMARDs other than HCQ and 202/266 (70.3%) MTX. Using 12 month MTX as the reference standard, the diagnostic performance of the criteria was moderate (area under curve, AUC (95% CI) 0.76 (0.69, 0.83). Using the proposed cut-off of 6, sensitivity (95% CI) was 0.87 (0.82, 0.91) and specificity 0.57 (0.44, 0.70). However, if we more properly considered all DMARDs other than HCQ as reference standard, the diagnostic performance was good, with a AUC (95% CI) of 0.80 (0.74, 0.87), with a sensitivity (95%CI) of 0.87 (0.81, 0.91) and a specificity of 0.63 (0.49, 0.76) for the cut-off of 6. Conclusions: The 2010 RA classification criteria show a moderate to good diagnostic performance in a the setting of EA, and this is in keeping with previous validation studies on external cohorts. In our population, sensitivity was very good, while specificity was slightly lower possibly due to treatment of UPA with HCQ. References: Aletaha D, et al. Ann Rheum Dis 2010;62:2569-81. Van der Linden MP, et al. Ann Rheum Dis 2011;63:1190-9. Disclosure of Interest: None Declared